Transkrypcja tekstu rosyjskiego na znaki polskiego alfabetu w relacjach z zesłania publikowanych na łamach czasopisma „Zesłaniec” - Dzienisiewicz, Daniel (Studia Rossica Posnaniensia, 2023)
The aim of the article is to analyze transcription errors occurring in the texts transcribed from Russian into the Polish alphabet which were published in the journal “Zesłaniec”. The results of the study show that the majority of errors are caused by Polish language interference and insufficient knowledge of the Russian language. Many errors are also influenced by the sounds of the Russian language. The obtained results are compared against the outcomes of (presented) previous analyses and high-frequency errors observed in studies to date. On the basis of the conducted analysis, the author proposes to modify the current Polish transcription system of the Russian language. He postulates that the rules used by the Polish Scientific Publishers PWN are replaced with a set of rules which would to a greater extent reflect the phonetic features of the Russian language as well as the transcription practices of Polish speakers.